Analisis Penerapan Bauran Pemasaran (Marketing Mix 7P’s) pada Kedai Kopi (Studi Kasus di Mosa Coffeehouse) - Tsalaatsa, Lazuardhi Ibnu; Yudha, Eka Purna (Universitas Galuh, 2024)
The business trends, particularly in the culinary sector, have been rapidly evolving over the past few decades. This study focuses on analyzing the marketing mix of 7Ps (Product, Price, Place, Promotion, People, Process, Physical Evidence) at Mosa Coffeehouse, a coffee shop in Bandung. The results of interviews and observations indicate a competition that can be enhanced by strengthening the unique values of each coffee shop. Mosa Coffeehouse's consumers, primarily females aged >21 years and millennials with a monthly pocket money of >Rp 2,000,000, show a preference for original Indonesian coffee products and a variety of food menu options. Prices are adjusted based on product quality, and the strategic location, professional service, appealing interior design, and comfortable facilities enhance the allure of the coffee shop. Despite incorporating most aspects of the marketing mix, weaknesses are identified in the promotion aspect, where the lack of a marketing team and the absence of a digital marketing strategy remain obstacles. Improvements in this aspect could enhance the visibility and competitiveness of Mosa Coffeehouse in the Bandung coffee shop market.